Development of the Architectural Design of the South Aceh Regency Library in Tapaktuan - Zuhrahmi DE; Ade Darmi Septiadi; Zulhadi Sahputra; Zulyaden Zulyaden (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
South Aceh Regency is one of the regencies located in Aceh Province, with Tapaktuan serving as its capital city. A regency library is a regional library that functions as a guiding library, reference library, deposit library, research library, and preservation library at the regency or municipal level. Currently, South Aceh Regency already has a library building; however, it is combined within the same building as the Department of Library and Archives. This condition makes the library less accessible to the public due to its closed nature and bureaucratic atmosphere. In South Aceh Regency, particularly in Tapaktuan, there are several higher education institutions such as polytechnics, academies, and colleges. In addition, there are also many schools and Islamic boarding schools. Based on interviews conducted with various groups, including the community, university students, and school students, there is strong interest in the development of a more open and accessible public library. Approximately 90% of respondents agreed with the plan to build such a facility. The main objective is to make it easier for the community, students, and pupils to access books and other sources of knowledge. By applying a metaphorical architectural approach, the building is expected to become a prominent landmark that encourages people to visit the regency library.